2017
DOI: 10.1016/j.athoracsur.2017.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Initial Experience With Lung Cancer Resection After Treatment With T-Cell Checkpoint Inhibitors

Abstract: T cell checkpoint inhibitors targeting the programmed death receptor-1 (PD-1) and its ligand (PDL-1) have recently been approved for the treatment of metastatic non-small cell lung cancer (NSCLC), but their safety and efficacy as neoadjuvant therapy are still undefined. Autoimmune toxicities, notably pneumonitis, are a particular concern in the perioperative setting. This series of 5 cases describes for the first time the safety and technical issues relating to pulmonary resection after checkpoint inhibitor th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 7 publications
0
78
1
1
Order By: Relevance
“…The authors of this study, which consisted mainly of skin resections and laparotomies, observed no major morbidity but did observe a wound complication rate of 22%. To our knowledge, aside from our initial case series of 5 patients, no study has examined the safety of pulmonary resection in patients who have received immunotherapy (6). …”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of this study, which consisted mainly of skin resections and laparotomies, observed no major morbidity but did observe a wound complication rate of 22%. To our knowledge, aside from our initial case series of 5 patients, no study has examined the safety of pulmonary resection in patients who have received immunotherapy (6). …”
Section: Commentmentioning
confidence: 99%
“…Similarly, the effect of the inflammatory response that is critical to the mechanism of action of these agents on the technical aspects of lung resection remains to be determined. Our institution previously published a case series on surgical resection in 5 initial patients receiving checkpoint inhibitors for advanced lung cancer (6); here, we incorporate those patients into a larger, more diverse cohort. The goal of this study was to analyze clinical, surgical, and outcomes data on patients referred for pulmonary resection following treatment with immune checkpoint inhibitors for previously metastatic or unresectable tumors at our quaternary care center.…”
Section: Introductionmentioning
confidence: 99%
“…There are currently no agreed guidelines on when to terminate immunotherapy before surgery and when to restart it afterwards. However, several small retrospective studies have reported outcomes in patients who underwent surgery during or after immunotherapy. In total, these studies reported 55 patients who underwent surgery within 1–147 days of the last dose of checkpoint inhibitor.…”
Section: Safety and Feasibility Of Surgery In Patients On Immunotherapymentioning
confidence: 99%
“…In total, these studies reported 55 patients who underwent surgery within 1–147 days of the last dose of checkpoint inhibitor. A wide range of procedures was performed, including lung resection, bowel resection with anastomosis, subcutaneous resection, craniotomy metastasectomy and lymph node dissection. No Clavien–Dindo grade III–IV postoperative complications were reported, suggesting that surgery may be safe and feasible in these patients.…”
Section: Safety and Feasibility Of Surgery In Patients On Immunotherapymentioning
confidence: 99%
“…Continued disease remission may be seen after discontinuation of checkpoint inhibitors, and the optimal duration of treatment remains undefined. 16 After 30 years of little progress in systemic therapy for lung cancer, the level of excitement in the oncologic community about this new therapeutic approach is understandable. However, the current progress represents a beginning rather than an end, and there is much work left to be done.…”
Section: Bryan M Burt Mdmentioning
confidence: 99%